Status of available major and micro nutrients in soils of Parmapur area of Mirzapur district of Uttar Pradesh - MAURYA, P. K.; RAJPUT, S .G.; SINGH, S.; KUMAR, P.; YADAV, B. (Journal of Soil and Water Conservation, 2021)
Fifty surface (0-25 cm) soil samples from Parmapur area of Mirzapur district were collected from three topo-sequence viz. low land, middle land and upland of the cultivated farmer fields, and were analyzed for different physico-chemical properties. The soil texture was determined clay loam to sandy clay loam. The study indicates that the area is deficient with respect to available N and P2O5, where as medium in organic carbon and available K2O status. Among the DTPA extractable micronutrients, Fe, Mn and Cu were found sufficient, whereas the soils were medium in Zn. The nutrient index values were low for available (1.65) P2O5 and (1.76) organic carbon, (1.49) N medium and for high K2O (2.30), DTPA extractable Zn (1.88) were medium, and high for Fe (2.72), Cu (2.58) and Mn (2.44), and low land are dominant with micronutrient and elevated organic carbon, while macronutrients are dominated in upland and the data on correlation studies among the soil properties, macro and micronutrient correlation significantly negative and positive relation. This information can be useful in developing management practices for the soils of cultivated farmer’s field of Parmapur area of Mirzapur district